2019
DOI: 10.3390/agronomy9100666
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Hosts of Pseudocercospora fijiensis Suggests Innovative Pest Management Programs for Black Sigatoka Disease in Banana Plantations

Abstract: Black Sigatoka is the main constraint to banana production worldwide, and epidemic outbreaks are continuously causing huge losses. Successful management of diseases requires a profound knowledge of the epidemiological factors that influence disease dynamics. Information regarding alternative hosts of Pseudocercospora fijiensis, the causal agent, is still very scarce. To date, only Heliconia psittacorum has been reported as an alternative plant host, and we hypothesized that other plants can house P. fijiensis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In this regard, in the climate of the South Pacific of Mexico, Black Sigatoka showed that the greatest damage (12 to 25% severity) occurs during the months of June to December, which coincides with the season of greatest rainfall [54]. In this period, symptoms appear in a state of spot between leaf nos.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, in the climate of the South Pacific of Mexico, Black Sigatoka showed that the greatest damage (12 to 25% severity) occurs during the months of June to December, which coincides with the season of greatest rainfall [54]. In this period, symptoms appear in a state of spot between leaf nos.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in the topic of pests and diseases were related to the incidence and severity in cultivation of heliconia caused by pathogens such as F. oxysporum f. sp. cubense, Pseudocercospora fijiensis; nematodes of the genus Meloidogyne, Helicotylenchus erythrinae, H. crenacauda, H. dihystera, Meloidogyne incognita, Pratylenchus zeae and Rotylenchulus reniformis, defoliators such as Cornops frenatum frenatum and mites, particularly specimens of Tropicoseius venezuelensis Baker & Yunker (Castro et al, 2008;Lemos et al, 2010;Sardinha et al, 2012;Sobrinho et al, 2012;Britto et al, 2015;Vázquez-Euán et al, 2019). Despite the affectations some authors recommend that the use of synthetic insecticides should be done only in extreme cases (Lemos et al, 2010).…”
Section: Productionmentioning
confidence: 99%
“…Another major challenge for the global production of Musaceae species is the development of cultivars resistant to biotic stressors, represented by their primary pests, the banana root borer ( Cosmopolites sordidus ) and the nematodes Meloidogyne spp., Pratylenchus coffeae , and Radopholus similis [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], and disease-causing pathogens, including banana bunchy top virus (BBTV) [ 20 , 21 ], Xanthomonas vasicola pv. musacearum causing bacterial wilt [ 22 , 23 , 24 , 25 ], Pseudocercospora fijiensis causing black Sigatoka [ 26 , 27 , 28 , 29 ], and Fusarium oxysporum f. sp. cubense (FOC) causing Fusarium wilt [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%